Improving Students’ Learning Outcomes Through Flashcard Media About My Culture For Grade 4 Elementary School - dewi, galuh kartika; Salsabila, Dwi Cahya (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Education is the main foundation for the progress of a nation. However, the quality of education in Indonesia is still a challenge that must be faced. Primary school education is the basic level for students in their education. Elementary school education contributes to building students knowledge base to be used in further education. Therefore, the implementation of learning in elementary schools must run optimally. This research aims to introduce Indonesian culture through the use of my culture flashcard media, which is useful for improving the learning outcomes of 4th-grade elementary school students. The research method used is Classroom Action Research (CAR) conducted in 4th grade at SDN Sukorejo Buduran with a total of 25 students. The data collection techniques employed are written tests and observations, while the data analysis technique involves comparing the percentage of learning mastery and observing student learning activities using my culture flashcard learning media in Cycle I and Cycle II. The results show that student mastery in the pre-action stage was 20% (5 students). In Cycle I, the mastery of cursive writing skills was 48% (12 students) in the pretest and 56% (14 students) in the posttest, with student activity reaching 75% in the “good” category. In Cycle II, the mastery of cursive writing skills increased to 56% (14 students) in the pretest and 80% (20 students) in the posttest, with student activity reaching 95% in the “very good” category. Thus, it can be concluded that the effort to improve students learning outcomes through the use of “Budayaku” flashcard media in 4th grade elementary school was successfully achieved.Keywords: Learning Outcomes, Flashcard Media My Culture